HEXITEC 2 × 2 tiled hard X-ray spectroscopic imaging detector system. (10th January 2022) - Jowitt, L.; Wilson, M.; Seller, P.; Angelsen, C.; Wheater, R.M.; Cline, B.; Schöne, D.; Lauba, F.; Goede, M.; Ball, R.; Verhoeven, M.; Gottseleben, G.; et al.
Abstract: HEXITEC is a spectroscopic imaging X-ray detector technology developed at the STFC Rutherford Appleton Laboratory for X-ray and γ-ray spectroscopic imaging applications. Each module has 80 × 80 pixels on a 250 μm pixel pitch, and has been implemented successfully in a number of applications. This paper presents the HEXITEC 2 × 2 detector system, a tiled array of 4 HEXITEC modules read out simultaneously, which provides an active area of 16 cm 2 . Systems have been produced using 1 mm thick Cadmium Telluride (CdTe) and 2 mm thick Cadmium Zinc Telluride (CdZnTe) sensor material. In this paper the system and data processing methods are presented, and the performance of the systems are evaluated. The detectors were energy calibrated using an 241 Am sealed source. Three types of charge sharing correction were applied to the data-charge sharing addition (CSA), charge sharing discrimination (CSD), and energy curve correction (ECC) which compensates for energy lost in the inter-pixel region. ECC recovers an additional 34 % of counts in the 59.5 keV peak in CdTe compared to the use of CSD; an important improvement for photon-starved applications. Due to the high frame rate of the camera system (6.3 kHz) an additional End of Frame (EOF) correction was also applied to 6.0 % of events to correct for signals that were readout whilst the signal was still forming. After correction, both detector materials were found to have excellent spectroscopic performance with a mean energy resolution (FWHM) of 1.17 keV and 1.16 keV for CdZnTe and CdTe respectively. These results successfully demonstrate the ability to construct tiled arrays of HEXITEC modules to provide larger imaging areas.